Anti‐tumour activity of oncolytic Western Reserve vaccinia viruses in canine tumour cell lines, xenografts, and fresh tumour biopsies. (10th October 2014) - Autio, K.; Knuuttila, A.; Kipar, A.; Ahonen, M.; Parviainen, S.; Diaconu, I.; Kanerva, A.; Hakonen, T.; Vähä‐Koskela, M.; Hemminki, A.
Abstract: Cancer is one of the most common reasons for death in dogs. One promising approach is oncolytic virotherapy. We assessed the oncolytic effect of genetically modified vaccinia viruses in canine cancer cells, in freshly excised tumour biopsies, and in mice harbouring canine tumour xenografts. Tumour transduction efficacy was assessed using virus expressing luciferase or fluorescent marker genes and oncolysis was quantified by a colorimetric cell viability assay. Oncolytic efficacy in vivo was evaluated in a nude mouse xenograft model. Vaccinia virus was shown to infect most tested canine cancer cell lines and primary surgical tumour tissues. Virus infection significantly reduced tumour growth in the xenograft model. Oncolytic vaccinia virus has antitumour effects against canine cancer cells and experimental tumours and is able to replicate in freshly excised patient tumour tissue. Our results suggest that oncolytic vaccinia virus may offer an effective treatment option for otherwise incurable canine tumours.